Early stimulation treatment provides complete sensory‐induced protection from ischemic stroke under isoflurane anesthesia. Issue 3 (16th April 2013) - Lay, Christopher C.; Jacobs, Nathan; Hancock, Aneeka M.; Zhou, Yi; Frostig, Ron D.
Abstract: Using a rodent model of ischemia [permanent middle cerebral artery occlusion (pMCAO)], previous studies demonstrated that whisker stimulation treatment completely protects the cortex from impending stroke when initiated within 2 h following pMCAO. When initiated 3 h post‐pMCAO, the identical treatment exacerbates stroke damage. Rats in these studies, however, were anesthetised with sodium pentobarbital, whereas human stroke patients are typically awake. To overcome this drawback, our laboratory has begun to use the anesthetic isoflurane, which allows rats to rapidly recover from pMCAO within minutes, to test stimulation treatment in awake rats and to determine whether isoflurane has an effect upon the pMCAO stroke model. We found no difference in infarct volume between pMCAO in untreated controls under either sodium pentobarbital or isoflurane, and the primary finding was that rats that received treatment immediately post‐pMCAO maintain cortical function and no stroke damage, whereas rats that received treatment 3 h post‐pMCAO exhibited eliminated cortical activity and extensive stroke damage. The only difference between anesthetics was the broad extent of evoked cortical activity observed during both functional imaging and electrophysiological recording, suggesting that the extent of evoked activity evident under isoflurane anesthesia is supported by underlying neuronal activity. Given the high degree of similarity with previous data, we conclude that the pMCAO stroke model is upheld with the use of isoflurane. This study demonstrated that the isoflurane‐anesthetised rat pMCAO model can be used for cerebrovascular studies, and allows for highly detailed investigation of potential novel treatments for ischemic stroke using awake, behaving animals. Abstract : Using a rat model of ischemia (permanent middle cerebral artery occlusion; pMCAO) we demonstrate that whisker stimulation can completely protect the cortex from impending stroke. Furthermore, the broad extent of evoked activity evident under isoflurane anesthesia plays a significant role in the protection from, or deterioration towards infarct. We conclude that the pMCAO model may be carried out using isoflurane, allowing for the future investigation of ischemic stroke in awake animals.